CAR-T therapy followed by allogeneic hematopoietic stem cell transplantation for refractory/relapsed acute B lymphocytic leukemia: Long-term follow-up results - Li, Zhihui; Yang, Keyan; Song, Yanzhi; Zhao, Yongqiang; Wu, Fan; Wen, Xiaopei; Li, Jing; Wang, Xianxuan; Xu, Teng; Zheng, Xiaoyu; Zheng, Qinglong; Wu, Tong (Frontiers in Oncology, 2023)
Background Patients with refractory/relapsed (r/r) acute B lymphocytic leukemia (B-ALL) can achieve complete response (CR) after chimeric antigen receptor T-cell (CAR-T) therapy, but recurrence occurs in the short term. To reduce recurrence and improve survival, CAR-T therapy followed by transplantation is a feasible option. We analyzed the long-term follow-up outcomes and the risk factors for allogeneic hematopoietic stem cell transplantation (allo-HSCT) after CR by CAR-T therapy in this study. Methods A total of 144 patients who underwent allo-HSCT after CAR-T therapy in our hospital were enrolled in this study. Target gene analysis was performed in 137 r/r B-ALL patients receiving allo-HSCT after CR by CAR-T therapy. Among the 137 patients, 87 were evaluated for germline predisposition gene mutations, and 92 were evaluated for tumor somatic gene mutations using NGS. The clinical factors, germline predisposition gene and somatic gene mutations associated with the prognosis of patients receiving transplantation after CAR-T therapy were analyzed using univariate Cox regression. Factors related to disease-free survival (DFS) and overall survival (OS) were analyzed using multivariate Cox regression analysis. Results In 137 r/r B-ALL patients, the 2-year cumulative incidence of recurrence (CIR), OS and DFS in patients receiving allo-HSCT after CAR-T therapy was 31.5%, 71.4%, and 60.5%, respectively. The 2-year OS and DFS in MRD-negative patients were 80.9% and 69.3%, respectively. Univariate Cox analysis showed that pretransplant MRD positivity, fungal infection, germline EP300 mutation and somatic TP53 mutation were associated with a poor prognosis after transplantation; a TBI-based regimen was a protective factor for survival and recurrence after transplantation. Multivariate Cox regression analysis showed that the TBI-based regimen was an independent protective factor for DFS, fungal infection and MRD positivity were independent risk factors for DFS, and tumor somatic TP53 mutation and germline EP300 mutation were independent risk factors for DFS and OS. Conclusion Germline EP300 mutation and tumor somatic TP53 mutation are poor prognostic factors for posttransplant recurrence and survival in r/r B-ALL patients achieving CR after CAR-T therapy. The prognostic risk factors should be considered in adjusting treatment strategies to improve the efficacy of clinical diagnosis and treatment.